Impact of Team Agility on Team Effectiveness: The Role of Shared Mental Models, Team Empowerment, and Team Reflexivity - Fabio Krüger (Junior Management Science (JUMS), 2023)
While more and more organizations are adopting team agility as a new work approach to cope better with change, research still lacks a proper understanding of the human-side of team agility. To investigate the effectiveness and the human-side of team agility, this study builds on the IMO-framework. Team agility is investigated as the input factor, shared mental models (SMM) and team empowerment as mediators, team performance and team satisfaction as outcomes and team reflexivity as moderator between the relationships of mediators and outcomes. Data was collected from 23 agile working teams (- = 3.48). Using linear regression both hypotheses, that team agility positively impacts SMM and team empowerment, were supported. This study found a significant total model effect for the relationship between team agility and team performance mediated by both, SMM and team empowerment. This study contributes to a better integration of the agile and teamwork literatures by identifying the roles of SMM and team empowerment on team effectiveness in an organizational context of team agility, as facilitating emergent team states.
Keywords: 650; Agile work; team agility; team effectiveness; shared mental models; team empowerment